DETECTION OF QUANTITATIVE LOCI CORRELATION WITH GROWTH TRAITES IN LOCAL QUAIL USING PCR- RFLP TECHNIQUE - S. A., Lajan; AL-Barzinji , Y.M.S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The objective of this study was to investigate the polymorphisms of three loci (SEMA3E, GH and TLX) that related with growth traits in local quail. A total of 720 birds (males and females) from three lines (desert, brown and white) were used. The results revealed that the effects of the line were significant on bird body weight and carcass weight and dressing percentage at 180 days at age. The Best Linear Unbiased Prediction (BLUP) value overall birds for body weight was ranged from -9.2173 to 10.0117, these results showed there were significant differences among high and low BLUP value groups in three quail lines under study. The PCR-RFLP results overall three lines showed that there were three, three and two alleles for SEMA3E, TLX and GH locus, respectively. This alleles gives twelve differences genotypes, the desert male quail with ACABAA genotype and desert female quail with AAABAA genotype (high group) for three loci under study give significantly higher body and carcass weight compared with another groups.  In conclusion results showed that there are agreements between BLUP values with PCR-RFLP results to select best birds and the selection process with molecular technique can play a major positive and rapid role to improve and increase growth traits in these lines of local quail in Iraqi Kurdistan region.